Prevalence, correlates and treatment needs of dental caries in patients attending a diabetic clinic in rural southwestern Uganda: a cross-sectional study - Arubaku, Wilfred; Tusubira, Deusdedit; Ssedyabane, Frank; Chamut, Steffany; Seymour, Brittany Anne; Siedner, Mark J.; Niyonzima, Vallence; Nabbanja, Juliet; Kakongi, Nathan; Kwizera, Godfrey; Maling, Samuel (BMC Oral Health, 2023)
Background: Diabetes mellitus is a complex heterogeneous metabolic disorder known to lead to several pathogenic disorders, and has a bidirectional relationship with oral health conditions. This study aimed at estimating the prevalence, treatment needs and correlates of dental caries among adult patients attending a diabetic clinic in Uganda. Methods: This was a cross-sectional study that used questionnaires to collect data on socio-demographic factors, diabetes history, oral health status, dental health care, dietary factors, lifestyle factors, and dental examination guided by the modified World Health Organization oral health questionnaire for adults. Results: We enrolled 239 participants, prevalence of dental caries was 71.6%, treatment need was nearly 100%, and mean DMFT was 3.82 (SD = 5.46). Dental caries experience was associated with being widowed. Conclusion: We found a high prevalence of dental caries experience and large treatment need among our participants. We recommend integration of oral health care into routine diabetic services in rural sub-Saharan Africa
Keywords: Dental caries; Diabetes; Treatment needs; Glycemic control; Uganda